Mycobacterium bovis deleted in mce2 and phoP loci protects C57BL/6 mice against tuberculosis - Garcia, Elizabeth Andrea (2016)
Mycobacterium bovis (Mb), the causative agent of bovine tuberculosis (bTB), infects cattle and other animals, including humans. In this study we found that a M. bovis knockout strain in phoP and mce2 operons protected C57BL/6 mice against virulent M. bovis challenge. The double mutant was significantly more attenuated than the parental M. bovis Δmce2 strain in immunodeficient mice.